Rethinking mobility in ancient histories of the Mediterranean and Amazonia - Peixoto, Renan Falcheti (2024)
The aim of this thesis is to explore migration and mobility through relational theories in an intercultural analysis of the ancient Mediterranean and Amazonia history. The underlying analogy for this comparison is of fractal geometry and network theory coalesced in the environmental studies of Mediterranean history. Over the past 20 years or so, post-Braudelian approaches have argued that the Mediterranean should not be defined solely by trait-lists of fixed geophysical characteristics. Instead, it should be understood as a complex system of interrelationships and multiple temporalities involving human and nonhuman components. This perspective opens new horizons for comparisons that extend beyond a shoestring definition of inland spaces. The case studies illustrate situations of cultural change and long-distance associations, such as the diffusion of bronze swords of the Naue II type in the Mediterranean basin at the end of the 2nd millennium BC and of polychrome ceramics in the Amazon basin throughout the 1st millennium AD. What representations of mobility have been reiterated in the social history of the respective regional archaeologies? Is it possible to define robust analytical parameters and concepts to unravel the complexities of social interaction? This thesis of uncanonical Ancient History seeks to make of the perspective of historical ecology good to think with, critically engaged in in geopolitically complex debates of the present, on the route of a decolonial thinking from the South to the North in archaeology. The ecological realities of the ancient Mediterranean and Amazonia present basic attributes, such as the fragmentation, diversification, and intercultural interconnectivity. Close and distant localities may be recursively interconnected and supra local identities continually reconfigured into contingent structures of the political landscape without necessarily involve transmission in the biological-genetic sense or single events of migration.